Managers of global change : the influence of international environmental bureaucracies - Biermann, Frank, 1967-; Siebenhüner, Bernd (MIT Press, 2009)
This title is an examination of the role and relevance of international bureaucracies in global environmental governance. After a discussion of theoretical context, research design, and empiral methodology, the book presents nine in-depth case studies of bureaucracies.